Carbon-Nanofibers-Based Micro-/Nanodevices for Neural-Electrical and Neural-Chemical Interfaces. (22nd April 2012) - Zhang, Hongzhi; Yu, Mei; Xie, Lei; Jin, Linlin; Yu, Zhe
Abstract : Carbon nanofibers (CNFs) have shown great potentials for development of micro-/nanodevices for neural interfaces due to their suitable properties, such as chemical stability, good electrical conductivity, ultramicro size with low electrical impedance, 3D structures with high surface-to-volume ratio, and long-term biocompatibility. In this paper, we review the applications of CNFs as neural-electrical interfaces and neural-chemical interfaces for neural recording and stimulation, electroconductive nanofibrous scaffolds for nerve tissue engineering, drug and gene delivery, and neurochemical sensing. The CNFs-based micro-/nanodevices provide new platforms to fine-tune electrical and chemical cues of neurons at subcellular nanoscale, which can be used for both fundamental studies of material-cell interactions and the development of chronically stable, implantable neural interface devices. Further development of this technology may potentially enable a highly multiplex closed-loop system with multifunctions for neuromodulation and neuroprostheses.